2020
DOI: 10.1101/2020.12.18.422986
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Easter Egg Weevil (Pachyrhynchus) genome reveals synteny in Coleoptera across 200 million years of evolution

Abstract: Patterns of genomic architecture across insects remain largely undocumented or decoupled from a broader phylogenetic context. For instance, it is unknown whether translocation rates differ between insect orders? We address broad scale patterns of genome architecture across Insecta by examining synteny in a phylogenetic framework from open source insect genomes. To accomplish this, we add a chromosome level genome to a crucial lineage, Coleoptera. Our assembly of the Pachyrhynchus sulphureomaculatus genome is t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 104 publications
(163 reference statements)
0
6
0
Order By: Relevance
“…More analyses are required to compare the design of Tagliacollo and Lanfear 2018 63 to the design we propose here to make a decisive decision of which scheme is optimal for UCE partitioning. The partition method we employ is the only one that accommodates the combination of neighboring or co-genic UCEs 51 In summation, we clearly demonstrated that many of the mimetic color patterns observed in sympatry are due to convergent evolution and not simply due to inheritance. Based on our observations in natural history collections, we hypothesize that convergence between these independent color pattern forms is likely driven by frequency dependent selection.…”
Section: Uce Partitioningmentioning
confidence: 74%
See 2 more Smart Citations
“…More analyses are required to compare the design of Tagliacollo and Lanfear 2018 63 to the design we propose here to make a decisive decision of which scheme is optimal for UCE partitioning. The partition method we employ is the only one that accommodates the combination of neighboring or co-genic UCEs 51 In summation, we clearly demonstrated that many of the mimetic color patterns observed in sympatry are due to convergent evolution and not simply due to inheritance. Based on our observations in natural history collections, we hypothesize that convergence between these independent color pattern forms is likely driven by frequency dependent selection.…”
Section: Uce Partitioningmentioning
confidence: 74%
“…Identifying UCE loci within genomic windows: We used methodologies that are similar to Van Dam et al 2020 51 for combining UCE loci. First, we identified UCE loci that are within 25 kb non-overlapping windows, as similar window sizes were used in Edelman et al 2019 59 .…”
Section: Species Tree Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying UCE loci within genomic windows: We used methodologies that are similar to Van Dam et al 2020 51 for combining UCE loci. First, we identified UCE loci that are within 25 kb non-overlapping windows, as similar window sizes were used in Edelman et al 2019 59 .…”
Section: Species Tree Analysesmentioning
confidence: 99%
“…using the "deleteEmptyCells" function, followed by removing any ragged ends of the matrix with the "trimEnds" function, with a minimum of four taxa present in the alignment. Below we expand on partitioning procedures to consider the potential site rate heterogeneity found in UCE loci as well as partition loci found in the same genomic window or potentially the same gene 51 . We use an alternative partitioning scheme from Van Dam et al 2017 and Tagliacollo and Lanfear 2018 62,63 .…”
Section: Species Tree Analysesmentioning
confidence: 99%